CALCULO AB-INITIO DE LA ESTRUCTURA ELECTRONICA DEL TOPACIO Al2SiO4(F,OH)2 - Flores, Luis (2006)
In this work the calculation was made ab-initio of the structure of bands and DOS of the Topaz with Fluoride (F) and Hydroxide (OH) in the fundamental state, with model TB-LMTO-ASA. The conventional cell of these 2 crystals does not present the same dimensions, due to the ion replacement F by molecules OH. The energy states will be affected by this new structure with OH, doing to vary the behavior of the bands, the DOS and therefore varying the optical properties of the crystal.